2016
DOI: 10.21608/edj.2016.95432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Pattern Construction Techniques on the Marginal Adaptation, Internal Fit and Fracture Resistance of Ips-Emax Press Crowns

Abstract: purpose: The purpose of this study was to evaluate the effect of pattern construction technique on the marginal accuracy, internal fitness and fracture resistance of E-max crowns. materials and methods: Thirty caries-free human maxillary first premolars were selected, cleaned by scaling, and stored in 0.9% standardized saline solution at room temperature. Using an industrial lathe machine, the teeth were prepared to receive all ceramic crowns with standardized dimensions of 6 degrees angle of convergence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Measurements Fig (4) : Comparison between the fracture strength of the tested groups were taken without cementation to omit the relative impact of the cementation process on the marginal fit and to allow determination of the system's precision. (37,40) In the current study, the resultant marginal gap mean values were found to be within the clinically acceptable range, while that of Group V was above this range by 0.9µm. as denoted by Christensen (1966), (41) who considered the clinically acceptable marginal gap range from 34 to 119μm for subgingival and 2 to 51μm for supragingival margins.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Measurements Fig (4) : Comparison between the fracture strength of the tested groups were taken without cementation to omit the relative impact of the cementation process on the marginal fit and to allow determination of the system's precision. (37,40) In the current study, the resultant marginal gap mean values were found to be within the clinically acceptable range, while that of Group V was above this range by 0.9µm. as denoted by Christensen (1966), (41) who considered the clinically acceptable marginal gap range from 34 to 119μm for subgingival and 2 to 51μm for supragingival margins.…”
Section: Discussionsupporting
confidence: 51%
“…After light polymerization of the new light polymerized modelling resins, high precision and stability are attained. (36)(37)(38) Saleh O et al(2016), (37) reported that the 3D printed patterns offered better marginal fit of IPS e.max Press crowns. They also recorded improved internal adaptation that consequently improved the fracture resistance of the crowns In this study, marginal adaptation was evaluated using a stereomicroscope.…”
Section: Discussionmentioning
confidence: 99%
“…(20,21) The marginal gaps of the uncemented vonlays were evaluated on the prepared tooth for standardization & to exclude the effect of cement. (22,23) Results revealed no statistically significant difference, where CD group showed the best marginal adaptation followed by VE then BC. The recorded marginal gap of all groups lies within the clinically acceptable range, as records were below 120μm.…”
Section: Discussionmentioning
confidence: 88%
“…(26) Crowns were not cemented to the prepared abutment, so that the effect of the cement film thickness was eliminated, as it was proved to increase the marginal gap (22) . Also, CAD/ CAM milling was chosen, to eliminate any human variations during construction, (29,30) as milling is capable of constructing restorations from prefabricated ceramic blocks with high degree of precision & margin adaptation provided by CAD/ CAM software, (26) {CD} crowns being constructed from a fully crystallized ceramic, were only polished without addition of a glaze to avoid subjecting them to additional glazing cycles & subsequently unavoidable marginal variations. Specially that the manufacturers claim that ZLS ceramics attain acceptable margins after restorations milling.…”
Section: Discussionmentioning
confidence: 99%